Association between neighborhood stressors and allostatic load in breast cancer survivors: the Pathways Study - Sangaramoorthy, Meera; Samayoa, Cathy; Inamdar, Pushkar P; Roh, Janise M; Valice, Emily; Hong, Chi-Chen; Kwan, Marilyn L; Ambrosone, Christine B; Kushi, Lawrence H; Gomez, Scarlett Lin; Shariff-Marco, Salma (American journal of epidemiology, 2025)
Allostatic load (AL) is an intermediary outcome through which neighborhood drivers of health may impact cancer survivorship outcomes. We examined associations of neighborhood stressors and AL in 2553 women with breast cancer recruited into the Pathways Study in 2006-2013. AL score was derived from biomarkers in the cardiovascular, metabolic, and immune domains of physiologic stress measured within 3 years after baseline. Neighborhood data were appended to participants' geocoded baseline addresses. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to estimate associations between neighborhood stressors and risk of higher AL score. Adjusting for age and stage, high AL was positively associated with low versus high neighborhood socioeconomic status (nSES; OR = 2.24; 95% CI, 1.61-3.12) and green space (OR = 1.55; 95% CI, 1.18-2.03), high versus low traffic (OR = 1.32; 95% CI, 1.01-1.72), crime (OR = 1.32; 95% CI, 1.05-1.67), household crowding (OR = 1.57; 95% CI, 1.22-2.01), and more versus no fast-food restaurants (OR = 1.50; 95% CI, 1.21-1.84). Associations remained for nSES and fast-food restaurants after coadjustment with other neighborhood stressors and for fast-food restaurants after additional adjustment with individual sociodemographic and lifestyle factors. Our preliminary findings can inform future studies of the physiologic effects of neighborhood stressors, which collectively may help improve survivorship outcomes for the growing population of breast cancer survivors.